Ambient Intelligence 4th International Joint Conference, AmI 2013, Dublin, Ireland, December 3-5, 2013. Proceedings - Augusto, Juan Carlos; Wichert, Reiner; Collier, Rem.; Keyson, David; Salah, Albert Ali.; Tan, Ah-Hwee.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 4th International Joint Conference an Ambient Intelligence, AmI 2013, held in Dublin, Ireland, in December 2013. The 15 revised full papers, 4 papers from the landscape track, 3 papers from the doctoral colloquium, and 6 demo and poster papers were carefully reviewed and selected from numerous submissions, and are presented with 6 workshop descriptions. The papers cover a variety of multi-disciplinary topics in computer science, human computer interaction, electrical engineering, industrial design, behavioral sciences, distributed devices, ubiquitous and communication technologies, pervasive computing, intelligent user interfaces and artificial intelligence.
Multi-disciplinary topics in computer science -- Human computer interaction -- Electrical engineering -- Industrial design -- Behavioral sciences -- Distributed devices -- Ubiquitous and communication technologies -- Pervasive computing -- Intelligent user interfaces -- Artificial intelligence.
Keywords: Computer science; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Computers and Society